Versatile coordination behaviors of a tetrapodal Schiff base ligand scaffold: formation of the dinuclear and trinuclear complexes and their antimicrobial activity. Issue 4 (16th February 2016) - Jiang, Guang-Qi; Wang, Ruo; Long, Li-Li; Sun, Tao; Yang, Zai-chang; Zhang, Yun-Qian; Zhang, Qian-Jun
Abstract: Four new complexes have been prepared and characterized from reaction of the tetrapodal Schiff base ligand 1, 1, 1, 1-tetrakis[(3-methoxysalicylaldimino)methyl]methane (H4 L) with Cu(II), Ni(II) and Cd(II). X-ray diffraction experiments revealed that1 ([Cu2 L·2H2 O]·H2 O) and2 ([Cu2 L·2CH3 OH]·3H2 O) are dinuclear complexes, with the same tetragonal pyramidal coordination geometries around their Cu(II) ions. Complex3 ([Ni2 L]·2H2 O) is dinuclear with two square planar Ni(II) ions coordinated to two pairs of the pendant branches of H4 L. Complex4 ([Cd3 (HL)2 ]·3H2 O) is a linear trinuclear species with three Cd(II) ions, which were intermolecularly coordinated to three pendant branches of two H4 L ligands via an uncommon intermolecular phenoxo oxygen face-sharing mode. The in vitro antimicrobial activities of H4 L and its complexes were evaluated against four micro-organisms ( Colibacillus, Staphylococcus aureus, Pseudomonas aeruginosa, and Bacillus subtilis ) using the tube-dilution method. The results revealed that3 showed good inhibitory activity against the Gram-positive bacteria S. aureus and B. subtilis with MIC values of 62.5 and 31.0 μg mL, respectively. Abstract :